As redes sociais e a responsabilidade dos autores pela divulgação de seu trabalho - Brait, Beth; Gontijo Rosa, Carlos; Cruz Pistori, Maria Helena; Lopes Fernandes, Bruna; Stella, Paulo Rogério; Godinho de Alcântara, Regina; Pucci Penteado de Faria e Silva, Adriana (Bakhtiniana. Revista de Estudos do Discurso, 2025)
Editorial 20.4